2019
DOI: 10.1111/chd.12712
|View full text |Cite
|
Sign up to set email alerts
|

Overview of transcatheter patent ductus arteriosus closure in preterm infants

Abstract: Clinically significant patent ductus arteriosus (PDA) has been associated with significant morbidity in extremely low birth weight (ELBW) infants. Current management of ELBW infants with hemodynamically significant PDA includes supportive treatment, pharmacological therapy, and surgical ligation. All of these therapeutic options have their advantages and limitations. More recently, transcatheter PDA closure has been described as a viable option in this population. In this paper, we provide a comprehensive revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Transcatheter closure at the bedside under echocardiography guidance-only has also been reported ( 44 ). Unfortunately, bedside procedure under echocardiography guidance has to be performed via trans-arterial route (femoral route) without fluoroscopy which carries increased risk of potentially severe life-threatening complications such as limb ischemia and more worryingly it has limited management options for disc embolization if it occurs ( 56 ). Hence, despite technical feasibility it is almost never performed on bedside in ELBW infants and smallest reported infant having this procedure successfully done was around 1,400 g. In comparison, when percutaneous PDA closure performed in in the catheter lab it has been performed successfully in infants as small as 700 g ( 50 52 ).…”
Section: Patient Selection and Organization Of The Proceduresmentioning
confidence: 99%
“…Transcatheter closure at the bedside under echocardiography guidance-only has also been reported ( 44 ). Unfortunately, bedside procedure under echocardiography guidance has to be performed via trans-arterial route (femoral route) without fluoroscopy which carries increased risk of potentially severe life-threatening complications such as limb ischemia and more worryingly it has limited management options for disc embolization if it occurs ( 56 ). Hence, despite technical feasibility it is almost never performed on bedside in ELBW infants and smallest reported infant having this procedure successfully done was around 1,400 g. In comparison, when percutaneous PDA closure performed in in the catheter lab it has been performed successfully in infants as small as 700 g ( 50 52 ).…”
Section: Patient Selection and Organization Of The Proceduresmentioning
confidence: 99%
“…14 On the one hand, PDA-HS has been associated with serious comorbidities, 3,4 however, closure methods, regardless of the type of method, also come with risks. 12,15,16 There is not always a consensus as to what gives the best prognosis for newborns, whether to wait or to close the DA. Sathanandam et al 17 , through a survey study, concluded that pediatric cardiologists are more in favor of the benefits of closure of the DA than neonatologists.…”
Section: Discussionmentioning
confidence: 99%
“…It is a closure method that is already widely used in older children, even considered as a first line above 6 kg. 12 In 2011, Bentham et al 10 reported a new echo-guided closure technique in newborns with very low birth weight. As a result, this closure method has become an increasingly valid option for premature NBs, with a reported success rates of over 80%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhaled nitric oxide also contributed to the bleeding because the exposure of nitric oxide might lead to a certain degree of coagulopathy (27). Transcatheter PDA closure in preterm infants has become an available intervention and several trials presented promising outcomes (28,29). The hemodynamic study can be measured during the cardiac catheterization, which even allows a test occlusion before PDA closure in pre-term infants with a bidirectional shunt.…”
Section: Discussionmentioning
confidence: 99%